Current issues in rheumatoid arthritis-associated interstitial lung disease. (November 2021) - Kelly, Clive; Emery, Paul; Dieudé, Philippe
Summary: Rheumatoid arthritis (RA) is associated with a ten-fold increased risk of interstitial lung disease (ILD). The presence of ILD in a patient with RA influences both prognosis and the choice of therapeutic intervention. Although there has been increasing awareness of the relevance of ILD to the outcome of patients with RA, there remains limited consensus around several important aspects of disease diagnosis and management. This Review emphasises two of the main areas in which a much greater standardisation of approach is urgently needed. First, the development of a screening approach based on established risk factors is a priority. Learning how to identify patients with RA-associated ILD early and then monitoring their condition to assess progression and measure the potential influence of therapeutic interventions is essential. Second, there is a need to consolidate the therapeutic evidence base to agree a standard approach to intervention. Although we already have a range of potentially effective treatments, further clinical trials are required to optimise therapeutic intervention.